2020
DOI: 10.1103/physreve.102.042136
|View full text |Cite
|
Sign up to set email alerts
|

Fokker-Planck approach to non-Gaussian normal diffusion: Hierarchical dynamics for diffusing diffusivity

Abstract: A theoretical framework is developed for the phenomenon of non-Gaussian normal diffusion that has experimentally been observed in several heterogeneous systems. From the Fokker-Planck equation with the dynamical structure with largely separated time scales, a set of three equations are derived for the fast degree of freedom, the slow degree of freedom and the coupling between these two hierarchies. It is shown that this approach consistently describes "diffusing diffusivity" and non-Gaussian normal diffusion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Since cell decision-making is a stochastic process of the continuous internal variable X, we can assume the existence of the Fokker-Planck description. When there exists a timescale separation between two dynamical variables, a Hierarchical Fokker-Planck equation [32] can be derived. In this section, we shall show how this formalism can be applied in cell decision-making and also will show how it helps us to study the origin of biophysical force in terms of the information-theoretic quantities as shown in Fig.…”
Section: Connection Between Hierarchical Fokker-planck Equation and B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since cell decision-making is a stochastic process of the continuous internal variable X, we can assume the existence of the Fokker-Planck description. When there exists a timescale separation between two dynamical variables, a Hierarchical Fokker-Planck equation [32] can be derived. In this section, we shall show how this formalism can be applied in cell decision-making and also will show how it helps us to study the origin of biophysical force in terms of the information-theoretic quantities as shown in Fig.…”
Section: Connection Between Hierarchical Fokker-planck Equation and B...mentioning
confidence: 99%
“…In the case of cell decision-making, microscopic dynamics have been studied, specifically in the context of active Brownian motion and cell migration using Langevin equations [22,30,31]. Understanding dynamics induced by a timescale separation at the mesoscopic scale, using Fokker-Planck equations, has been studied only recently by S. Abe [32]. Specifically, we will assume a timescale separation where cell decision time, when internal states evolve, is slower than the characteristic time of the variables that belong to the cellular microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Since cell decision making is a stochastic process of the continuous internal variable , we can assume the existence of the Fokker–Planck description. When there exists a timescale separation between two dynamical variables, a hierarchical Fokker–Planck equation [ 32 ] can be derived. In this section, we shall show how this formalism can be applied in cell decision making and also will show how it helps us to study the origin of biophysical forces in terms of the information-theoretic quantities as shown in Figure 1 .…”
Section: Connection Between Hierarchical Fokker–planck Equation and B...mentioning
confidence: 99%
“…In the case of cell decision making, microscopic dynamics have been studied, specifically in the context of active Brownian motion and cell migration using Langevin equations [ 22 , 30 , 31 ]. Understanding dynamics induced by a timescale separation at the mesoscopic scale, using Fokker–Planck equations, was studied only recently by S. Abe [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a generalization of the Fokker-Planck theory, in which the diffusion coefficient is not a constant but a fluctuating variable that may describe the effects originating from heterogeneity of the crust and a complex landscape of the stress distribution at faults, and see how such an theory can explain the features of the temporal pattern of aftershocks. For this purpose, "a modified version" of the approach recently proposed in Reference [15] is employed for representing the dynamical hierarchy. It is shown that the relaxation function in Equation (2) can be obtained for the subsystem defined through elimination of the fluctuating diffusivity.…”
Section: Introductionmentioning
confidence: 99%